(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the treatment outcomes of postpartum hemorrhage due to uterine atony following vaginal delivery at the National Hospital of Obstetrics and Gynecology from June 2024 to June 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 59 cases of postpartum hemorrhage following vaginal delivery that were managed at the National Hospital of Obstetrics and Gynecology during the study period. Results: The age group 25–29 years accounted for the highest proportion, followed by the 30–34 age group. The most common risk factors were precipitous labor, macrosomia, and a considerable proportion of cases with unidentified risk factors. Medical management was applied in most cases and achieved complete success; interventional procedures were partially successful, and all unsuccessful cases were subsequently managed surgically, leading to a 100% overall hemorrhage control rate. Most patients required blood transfusion, with a moderate average volume administered. The average post-hemorrhage treatment duration was short, with the majority recovering within three days, and no complications were recorded. Conclusion: Stepwise management of postpartum hemorrhage due to uterine atony following clinical protocols proved to be highly effective and safe. Early intervention and adherence to standardized procedures played a pivotal role in successful hemorrhage control and minimizing complications. Conservative treatment approaches remain central in obstetric clinical practice.